2011
DOI: 10.1093/ejo/cjr018
|View full text |Cite
|
Sign up to set email alerts
|

Association between root resorption incident to orthodontic treatment and treatment factors

Abstract: The purpose of this study was to clarify the prevalence and degree of root resorption induced by orthodontic treatment in association with treatment factors. The files of 243 patients (72 males and 171 females) aged 9-51 years were randomly selected from subjects treated with multi-bracket appliances. The severity of root resorption was classified into five categories on radiographs taken before and after treatment. The subjects were divided into extraction (n = 113 patients, 2805 teeth) and non-extraction (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 24 publications
5
71
0
8
Order By: Relevance
“…We superimposed the tracings by means of the ''best fit of anatomical structures'' with a primary emphasis on the concordance of the palatal plane (ANS-PNS) and ANS for the maxilla and mandibular plane (gonion-menton) and menton for the mandible. 11 The horizontal movement (Dx) and vertical movement (Dy) of the maxillary and mandibular central incisal edges were measured using an X-Y coordinate system, defined as the x-axis parallel to the palatal plane or mandibular plane and the y-axis perpendicular to the x-axis passing through the ANS or menton. The þ x value was defined as the direction of protraction and the þ y value as the direction of extrusion.…”
Section: Evaluation Of Central Incisor Movement On Lateral Cephalogramsmentioning
confidence: 99%
“…We superimposed the tracings by means of the ''best fit of anatomical structures'' with a primary emphasis on the concordance of the palatal plane (ANS-PNS) and ANS for the maxilla and mandibular plane (gonion-menton) and menton for the mandible. 11 The horizontal movement (Dx) and vertical movement (Dy) of the maxillary and mandibular central incisal edges were measured using an X-Y coordinate system, defined as the x-axis parallel to the palatal plane or mandibular plane and the y-axis perpendicular to the x-axis passing through the ANS or menton. The þ x value was defined as the direction of protraction and the þ y value as the direction of extrusion.…”
Section: Evaluation Of Central Incisor Movement On Lateral Cephalogramsmentioning
confidence: 99%
“…The etiology is multifactorial: individual biologic characteristics, genetic predisposition and the effect of orthodontic forces. 6 Studies based on microscopic analysis show a prevalence of 100% after the orthodontic treatment.…”
Section: 212941mentioning
confidence: 99%
“…4,5 On the root level, there may appear to be root resorption, early closure of root apex, or ankylosis. [6][7][8] Pulpal complications during orthodontic procedures can be ischemia, pulpitis, or even necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Individual Variations in the Hardness and Elastic Modulus of the Human Cementum Masaru Yamaguchi 1) , Eriko Yao-Umezawa 1) , Yasuhiro Tanimoto 2) , Mami Shimizu 1) , Jun Kikuta 1) , Takuji Hikida 1) , Momoko Takahashi-Hikida 1) , Satoshi Horihata 3) Introduction Orthodontically-induced inflammatory root resorption (OIIRR) is an unwanted side effect of orthodontic treatment. Motokawa et al 1) reported that teeth undergoing orthodontic treatment may develop some degree of OIIRR.…”
Section: Originalmentioning
confidence: 99%
“…Motokawa et al 1) reported that teeth undergoing orthodontic treatment may develop some degree of OIIRR. It has been reported that 2%-5% of orthodontic patients experience more than 5 mm of resorption during orthodontic treatment with fixed appliances.…”
Section: Originalmentioning
confidence: 99%